PEMBELAJARAN MENULIS TEKS EKSPLANASI MENGGUNAKAN METODE DISCOVERY LEARNING - Sri Anjani; Teti Sobari; Eli Syarifah Aeni (IKIP Siliwangi, 2020)
Abstract The background of this research is the lack of students' interest in writing activities, especially writing explanatory texts. Writing is an activity to express ideas and ideas through writing media. These problems can occur due to several things, for example teacher and student factors who have an important role in the achievement of learning. Therefore, researchers try to provide solutions to these problems so that students' interest in writing explanatory text can increase. This study aims to describe: (1) the use of discovery learning method in class VIII students in learning to write explanatory text. (2) the results of the analysis of the students' ability in writing explanatory text using discovery learning methods. The research method used in this research is descriptive qualitative method. The subjects in this study were 29 students of class VIII. The results of this study indicate that the use of discovery learning method in learning to write explanatory text is carried out in accordance with the planned steps. In addition, the students' ability to write explanatory texts in grade VIII was quite good and the final average score obtained was 77.9.